Herd management information systems to support cattle population research : the VAMPP® case = Sistemas de gestión de hato para apoyar investigación en poblaciones ganaderas : el caso VAMPP® - Sánchez Hernández, Guadalupe Zazil
Introduction. Livestock information systems, besides being indispensable for the daily management of the herd, can serve as a basis for research at the population level. Objective. The objective of the study was to analyze the role of the VAMPP® system as a source of information for cattle population research over 32 years of evolution in Costa Rica. Materials and methods. A statistical analysis of the system database (VAMPP®) covering the period between 1987 and 2018 was carried out. Trends in the dissemination and adoption of the system were evaluated according to period, area, production system, and herd size. The use of information for the exploration of trends by breed and area was exemplified. The contribution of the system at the academy level and production of scientific literature was quantified. Results. 2285 herds (88.8 % specialized dairy and 11.2 % dual purpose) were counted with an average of 9.4±7.9 years of follow-up in the VAMPP® system. The areas with greater diffusion were the very humid premontane forest (29 %) and very humid tropical forest (25 %). The average size of the herd was 124±255 adult cows. The system contains records on 404 316 cows, mostly of Holstein (36.3 %), Jersey (24.6 %), and Holstein×Jersey (20.9 %) breeds. The database includes information on 1,249,557 calvings, 16,223,260 records of daily milk production, and 443,108 health events, predominantly related to mastitis (35.6 %) and laminitis (14.1 %). The system has been used for the elaboration of at least 74 investigations leading to academic degrees and the production of 71 scientific articles, mainly related to health and genetic issues. Conclusion. The information obtained from the VAMPP® system has allowed a detailed characterization of the productive performance of local dairy cattle.